Peningkatan Kualitas Pendidikan Anak SD Melalui Program Pendampingan Belajar di Masa Pandemi Desa Pagutan Kecamatan Manyaran Kabupaten Wonogiri - Azizatul Janah; Fendi Krisna Rusdiana (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2022)
Student learning is generally carried out face-to-face and interacts directly between teachers and students in distributing knowledge in a supportive learning environment. In this case, it must be supported by an effective learning process and create a learning atmosphere that makes students interested in learning, so that learning runs smoothly and can understand children about the material that has been conveyed. However, the dynamics of learning in Indonesia are currently experiencing obstacles due to the Covid-19 outbreak which makes students have to undergo online learning activities. Many students have difficulty understanding the material and lack of student motivation in participating in learning during the Covid-19 Pandemic. This of course results in learning motivation to decrease, because itu cannot overcome the difficulties faced in learning. Departing form the assets of elementary school children who experience problems in understanding various knowledge, both religious knowledge and general knowledge, the KPM-DDR IAIN Ponorogo students seek to facilitate the children of the Pagutan village Elementary School to improve the quality of children’s education to form a generation that is knowledgeable to become a generation that can build their area in to a more advanced area in terms of education and broad-minded in order to develop various assets in the local village in the future. One the of the efforts to overcome educational problems during the Covid-19 Pandemic is through learning assistance activities which area part of the student work program of the Online Community Service Lecture from Home at IAIN Ponorogo together with Improving the Quality of Education during the Covid-19 Pandemic. This work program is expected to help elementary school children in overcoming existing problems, so that children can understand the material, are motivated to always learn and always follow online learning.